MINAT GENERASI MUDA KEPADA PELESTARIAN GAMELAN JAWA DI KOMUNITAS GAMELAN MUDA SAMURTI ANDARU LARAS - Ananda, Salma (Studi Budaya Nusantara, 2022)
This study aims to determine the factors driving the interest of the younger generation in the preservation of Javanese gamelan in the Samurti Andaru Laras Young Gamelan Community and their conservation efforts. This study uses a qualitative method with data collection techniques used are interviews, documentation, literature and observation. The method used in data analysis is data reduction, data presentation and conclusion. The data source of this research uses primary data and secondary data. The results of the study concluded that the motivating factor for the young generation to preserve Javanese gamelan in the Samurti Andaru Laras Young Gamelan Community was driven by internal factors, namely the desire from within oneself and external factors, namely coming from the family. The efforts to preserve Javanese gamelan are carried out by the Samurti Andaru Laras Young Gamelan Community through development and utilization methods. Methods of development through staging innovations with collaboration of modern musical instruments, implementation of modern instruments in composing music, as well as performing collaborations with modern bands in staging through collaboration of modern musical instruments, composing music with modern instruments, and collaborating with modern bands. Utilization efforts are made by opening workshops and beginner classes for the general public who want to play Javanese gamelan and perform Javanese gamelan performances at every event, wedding accompaniment or competition.